2020
DOI: 10.1093/ckj/sfaa212
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous iron therapy and the cardiovascular system: risks and benefits

Abstract: Anaemia is a common complication of chronic kidney disease (CKD). In this setting, iron deficiency is frequent because of the combination of increased iron needs to sustain erythropoiesis with increased iron losses. Over the years, evidence has accumulated on the involvement of iron in influencing pulmonary vascular resistance, endothelial function, atherosclerosis progression and infection risk. For decades, iron therapy has been the mainstay of therapy for renal anaemia together with erythropoiesis-stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 82 publications
0
10
0
1
Order By: Relevance
“…The optimal management of iron deficiency in patients with CKD is unclear with some evidence suggesting benefit with intravenous iron while others raising concerns about adverse effects 10 , 23 . These concerns surround issues such as oxidative stress leading to endothelial and cardiac dysfunction via lipid peroxidation, cytotoxicity and activation of monocytes 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The optimal management of iron deficiency in patients with CKD is unclear with some evidence suggesting benefit with intravenous iron while others raising concerns about adverse effects 10 , 23 . These concerns surround issues such as oxidative stress leading to endothelial and cardiac dysfunction via lipid peroxidation, cytotoxicity and activation of monocytes 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the findings of iron deposition within CUA specimens, there have been several proposed theories as to why iron might be associated with CUA pathogenesis, such as its known toxic effect in overload, including iron-induced oxidative stress, and its role in conditions such as atherosclerosis and vascular calcification. Research into atherosclerosis has revealed elevated levels of vascular cell adhesion molecules (VCAMs) and an increase in intima-media thickness with iron excess or supplementation [ 24 ]. Iron accumulation is also found within atherosclerotic plaques, particularly those which are symptomatic [ 24 ].…”
Section: Mechanistic Insights On the Role Of Iron In The Pathogenesis...mentioning
confidence: 99%
“…Research into atherosclerosis has revealed elevated levels of vascular cell adhesion molecules (VCAMs) and an increase in intima-media thickness with iron excess or supplementation [ 24 ]. Iron accumulation is also found within atherosclerotic plaques, particularly those which are symptomatic [ 24 ]. Increased quantities of soluble adhesion molecules were found in CKD patients who received iron sucrose, with cumulative iron dose correlating with increased intima-media thickness [ 24 ].…”
Section: Mechanistic Insights On the Role Of Iron In The Pathogenesis...mentioning
confidence: 99%
“…Results from a prospective, multicentric, randomized controlled study of more than 2000 patients undergoing hemodialysis (HD) support the efficacy and safety of relatively high-dose iv iron therapy among hemodialysis-dependent patients treated with ESA [ 20 , 121 ]. Monthly administration of 400 mg iv iron in patients with serum ferritin < 700 µg/L and TSAT ≤ 40% decreases ESA use and lowers the risk of all-cause death, nonfatal myocardial infarction, nonfatal stroke, and hospitalization for heart failure compared with iv iron administered in a reactive fashion for ferritin < 200 µg/L or TSAT < 20% [ 20 , 121 ]. FIND-CKD study in ND-CKD patients demonstrated that iv iron dosed to target ferritin of 400–600 µg/L compared with oral iron quickly reached and maintained Hb.…”
Section: Iron Supplementationmentioning
confidence: 99%